Total IgE levels in patients with hematologic malignancies - Parisa Amjadi, Ph.D; Fatemehsadat Hosseini, M.D; Ehsan Zaboli, M.D; Mohammad Eslami-Jouybari, M.D; Hossein Asgarian-Omran, Ph.D; Akbar Hedayatizadeh-Omran, M.D, Ph.D; Versa Omrani-Nava, M.Sc; Reza Alizadeh-Navaei, M.D, Ph.D (World Allergy Organization Journal)
Background: Immune system compartments have a crucial role in the progression or suppression of cancer. Hematologic malignancies are among the most common cancers, and there is conflicting research regarding the role of their relationship with allergies and IgE levels. This study aimed to compare total IgE levels in patients with hematologic malignancies to those in non-cancer controls. Methods: In this cross-sectional study in 2023, sixty patients with hematological malignancies and 90 non-cancer patients attending Sari Imam Hospital were evaluated for total IgE levels along with demographic data. The convenience sampling method was used for the selection of both patients and controls. IgE levels were measured in both groups ELISA method. The analysis was performed using SPSS 20. Results: The most common types of malignancy were ALL (23.3%) and multiple myeloma (23.3%). The median IgE level in patients (7.08, IQR:2.07–19.07) was significantly lower than the control group (42.41, IQR:11.99–145.57). The odds ratio for hematological malignancy associated with low total IgE was 6.79 (CI 95%: 2.90–15.92). After adjusting for age and sex, the adjusted odds ratio increased to 15.89 (CI 95%: 4.14–60.95). Conclusion: Patients with hematological cancers have significantly lower IgE levels compared with individuals with no cancer.